2020
DOI: 10.3390/pharmaceutics12060501
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Cationic Antimicrobial Peptides (eCAPs) to Combat Multidrug-Resistant Bacteria

Abstract: The increasing rate of antibiotic resistance constitutes a global health crisis. Antimicrobial peptides (AMPs) have the property to selectively kill bacteria regardless of resistance to traditional antibiotics. However, several challenges (e.g., reduced activity in the presence of serum and lack of efficacy in vivo) to clinical development need to be overcome. In the last two decades, we have addressed many of those challenges by engineering cationic AMPs de novo for optimization under test conditions that typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 162 publications
(239 reference statements)
0
39
0
Order By: Relevance
“…It has been suggested that cationicity and acetylation at N -terminal contribute to improve the activity of AMPs [ 29 ]; Therefore, three positive amino acids and/or acetylation at N -terminal were further introduced on the basis of two nonapeptides. As a consequence, we constructed three novel dodecapeptides including WR-12, WRK-12 and WKK-12 with acetylation at the N -terminus and amidation at the C -terminus.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that cationicity and acetylation at N -terminal contribute to improve the activity of AMPs [ 29 ]; Therefore, three positive amino acids and/or acetylation at N -terminal were further introduced on the basis of two nonapeptides. As a consequence, we constructed three novel dodecapeptides including WR-12, WRK-12 and WKK-12 with acetylation at the N -terminus and amidation at the C -terminus.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies on AMPs reveal a contextual problem—namely, AMPs not behaving the same in vivo as in vitro. In addition to showing a different behaviour with changing pH and ion concentrations, some AMPs can bind to plasma proteins in serum, which renders the AMPs ineffective 49 . We thus propose further investigation of PLNC8 αβ, where in vivo experiments are a priority.…”
Section: Discussionmentioning
confidence: 99%
“…Bactericidal effect of the APIM-peptide in planktonic MRSE cultures was already detected after 30 min incubation ( Figure 1A ), while it took 8 h before vancomycin completely killed the planktonic culture ( Figure 1B ). An engineered cationic antimicrobial peptide called WLBU2, now in phase 1 trials for treatment of PJIs ( Deslouches et al, 2020 ), has shown comparable effect as APIM-peptides on staphylococcus with regard to rapid bactericidal effects; S. aureus where killed at 2x MIC already after 10 min ( Mandell et al, 2017 ). We detected re-growth in less than 50% of the time-killing experiments using 1x MIC of APIM-peptide ( Supplementary Figure S1 ); however, this is likely due to slightly different assay conditions than in the MIC-assay.…”
Section: Discussionmentioning
confidence: 99%